2015
DOI: 10.1210/en.2014-1707
|View full text |Cite
|
Sign up to set email alerts
|

PK11195 Effect on Steroidogenesis Is Not Mediated Through the Translocator Protein (TSPO)

Abstract: Translocator protein (TSPO) is a mitochondrial outer membrane protein of unknown function with high physiological expression in steroidogenic cells. Using TSPO gene-deleted mice, we recently demonstrated that TSPO function is not essential for steroidogenesis. The first link between TSPO and steroidogenesis was established in studies showing modest increases in progesterone production by adrenocortical and Leydig tumor cell lines after treatment with PK11195. To reconcile discrepancies between physiological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 38 publications
2
83
2
Order By: Relevance
“…This result was again inconsistent with another early report that monoallelic disruption of TSPO in the R2C Leydig cell line obliterated its steroidogenic potential and caused phenotypic abnormality [7]. However, changes in phenotype or issues with viability were not observed in three independent clones of the MA-10:TspoD/D cells examined in the recent study [47], suggesting that TSPO deletion does not affect essential cellular functions. Moreover, when MA-10:TspoD/D cell clones were used to examine the steroidogenic ability of the TSPO-binding chemical PK11195, both control and TSPO-deficient cells showed identical increases in steroid hormone production [47].…”
Section: Box 2 the Mptcontrasting
confidence: 88%
See 2 more Smart Citations
“…This result was again inconsistent with another early report that monoallelic disruption of TSPO in the R2C Leydig cell line obliterated its steroidogenic potential and caused phenotypic abnormality [7]. However, changes in phenotype or issues with viability were not observed in three independent clones of the MA-10:TspoD/D cells examined in the recent study [47], suggesting that TSPO deletion does not affect essential cellular functions. Moreover, when MA-10:TspoD/D cell clones were used to examine the steroidogenic ability of the TSPO-binding chemical PK11195, both control and TSPO-deficient cells showed identical increases in steroid hormone production [47].…”
Section: Box 2 the Mptcontrasting
confidence: 88%
“…However, changes in phenotype or issues with viability were not observed in three independent clones of the MA-10:TspoD/D cells examined in the recent study [47], suggesting that TSPO deletion does not affect essential cellular functions. Moreover, when MA-10:TspoD/D cell clones were used to examine the steroidogenic ability of the TSPO-binding chemical PK11195, both control and TSPO-deficient cells showed identical increases in steroid hormone production [47]. This finding indicated that the effect of PK11195 on steroidogenesis in MA-10 cells is not mediated through TSPO, suggesting that previous studies reporting the pharmacological link between TSPO and steroidogenesis in this cell line and at the same range of concentrations [5,6] were probably describing off-target effects.…”
Section: Box 2 the Mptmentioning
confidence: 72%
See 1 more Smart Citation
“…The cells were passaged once and frozen for use in experiments. Generation and culture of TSPO deleted MA-10 cells (MA-10:Tspo ⌬/⌬ cells) has been previously described (8). Human colon cancer cell lines were obtained from ATCC and cultured using recommended methods.…”
Section: Tspomentioning
confidence: 99%
“…Furthermore, in some cases, as reported for etifoxine on frog hypothalamic explants [93], the increase in steroidogenesis produced by TSPO ligand may be mediated by TSPO independent mechanisms [97].…”
Section: Tspo and The Control Of Neuroactive Steroid Levelsmentioning
confidence: 83%